Pediatric Primary Adrenal Insufficiency: A 21-year Single Center Experience - Emine Çamtosun; İsmail Dündar; Ayşehan Akıncı; Leman Kayaş; Nurdan Çiftçi (Galenos Yayincilik, 2021)
Objective:Primary adrenal insufficiency (PAI) is a rare but potentially life-threatening condition. In childhood, PAI is usually caused by monogenic diseases. Although congenital adrenal hyperplasia (CAH) is the most common cause of childhood PAI, numerous non-CAH genetic causes have also been identified.Methods:Patients aged 0-18 years and diagnosed with PAI between 1998 and 2019 in a tertiary care hospital were retrospectively evaluated. After the etiologic distribution was determined, non-CAH PAI patients were evaluated in detail.Results:Seventy-three PAI patients were identified. The most common etiology was CAH (69.9%, n=51). Non-CAH etiologies accounted for 30.1% (n=22) and included adrenoleukodystrophy (ALD; n=8), familial glucocorticoid deficiency (n=3), Triple A syndrome (n=5), autoimmune adrenalitis (n=1), adrenal hypoplasia congenital (n=1), IMAGe syndrome (n=1), and other unknown etiologies (n=3). The median age at the time of AI diagnosis for non-CAH etiologies was 3.52 (0.03-15.17) years. The most frequent symptoms/clinical findings at onset were hyperpigmentation of skin (81.8%), symptoms of hypoglycemia (40.9%), and weakness/fatigue (31.8%). Hypoglycemia (50.0%), hyponatremia (36.4%) and hyperkalemia (22.7%) were prominent biochemical findings. Diagnosis of specific etiologies were proven genetically in 13 of 22 patients. A novel p.Q301* hemizygous frameshift mutation of the DAX1 gene was identified in one patient.Conclusion:Etiology was determined in 86.3% of children with non-CAH PAI through specific clinical and laboratory findings with/ without molecular analysis of candidate genes. ALD was the most common etiology. Currently, advanced molecular analysis can be utilized to establish a specific genetic diagnosis for PAI in patients who have no specific diagnostic features.